Presentation of Tuberculous Meningitis - Haji, Salma (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To find out the frequency of presentation of Tuberculous meningitis in different stages and to assess the role of Cerebrospinal fluid analysis and Magnetic Resonance imaging in diagnosis. Methodology: This descriptive observational study was conducted at neurology ward at JPMC Karachi from July 2018 - December 2019. Diagnosed patients of tuberculous meningitis above 12 years of age included in the study and were classified into three stages. Stage 1 included non-specific symptoms like headache, vomiting, fever and anorexia without impaired level of consciousness. Stage 2 patients were altered level of consciousness or focal neurological deficit without coma. Stage 3 patients included coma, Cerebrospinal fluid analysis and Magnetic Resonance imaging findings were recorded. Mortality was recorded in Performa. Other variables like age, sex, residence etc. were recorded. Data was analyzed by SPSS version 24. Results: Patients were 110, presented in stage 1 were 30%( 33/110). In stage 2, 60 %( 66/110) and in stage 3, 10%(11/110). Mortality was 10% and patients who expired were presented in stage 3. Tuberculous Meningitis patients presented with neck stiffness 98.18(108/110), headache 70% (77/110), anorexia 60%(66/110), sign of meningeal irritation 50%(55/110) and 40%(44/110) cranial nerve palsies 40%. The Cerebrospinal fluid findings were raised protein (63.63) lymphocytosis 99.91%(109/110) low glucose 98.18%(108/119) Magnetic Resonant Imaging findings were meningeal enhancement 49.09%(54/110). Conclusion: Tuberculous meningitis patients presented predominantly in stage 2(60%) then stage 1 (30%) and in stage 3 (10%). Cerebrospinal fluid analysis and Magnetic Resonance Imaging are good diagnostic investigation for Tuberculous Meningitis. Sign and symptoms were usually non-specific. Key Words: Tuberculous Meningitis, Cerebrospinal fluid, presentation of Tuberculous meningitis, stages of Tuberculous Meningitis